Brief angiotensin converting enzyme inhibitor treatment in young spontaneously hypertensive rats reduces blood pressure long-term - Harrap, S B; Van der Merwe, W M; Griffin, S A; Macpherson, F; Lever, A F (Hypertension (Dallas, Tex. 1979), 1990)
Our study examines the long-term cardiovascular effects after a brief period of angiotensin converting enzyme (ACE) inhibitor treatment in young spontaneously hypertensive rats (SHR). SHR were treated with perindopril (3 mg/kg/day) by gavage from 2 to 6, from 6 to 10, or from 2 to 10 weeks of age. Systolic blood pressure was measured in the tail weekly until 25 weeks of age. Corresponding control groups received distilled water for the same periods. In each treatment group blood pressure was reduced significantly during treatment, rose when treatment stopped, but plateaued significantly below control SHR thereafter. This difference in blood pressure at 25 weeks of age was due to reduced total peripheral resistance as determined by microsphere methods, but plasma renin activity and angiotensin II concentrations were not different. Cardiac hypertrophy was also reduced in treated SHR. In a separate experiment, perindopril treatment from 6 to 10 weeks of age resulted in a significant reduction in the media/lumen ratios of mesenteric resistance vessels at 32 weeks of age. Concomitant administration of angiotensin II with perindopril from 6 to 10 weeks of age not only prevented the long-term effects on blood pressure seen with perindopril treatment alone but was associated with cardiovascular hypertrophy in excess of untreated control SHR. Finally, perindopril given for a shorter period (6 to 7 weeks) or later in life (20 to 24 weeks) had no significant long-term effects on blood pressure. These results demonstrate that a 4-week period of ACE inhibitor treatment in young SHR is sufficient to prevent the full expression of genetic hypertension and cardiovascular hypertrophy and that angiotensin II might be important in the development of hypertension in this model, its role in later life being less important.